Whether to Save a Robot or a Human: On the Ethical and Legal Limits of Protections for Robots - Mamak, Kamil (Frontiers in Robotics and AI, 2021)
Proponents of welcoming robots into the moral circle have presented various approaches to moral patiency under which determining the moral status of robots seems possible. However, even if we recognize robots as having moral standing, how should we situate them in the hierarchy of values? In particular, who should be sacrificed in a moral dilemma – a human or a robot? This paper answers this question with reference to the most popular approaches to moral patiency. However, the conclusions of a survey on moral patiency do not consider another important factor, namely the law. For now, the hierarchy of values is set by law, and we must take that law into consideration when making decisions. I demonstrate that current legal systems prioritize human beings and even force the active protection of humans. Recent studies have suggested that people would hesitate to sacrifice robots in order to save humans, yet doing so could be a crime. This hesitancy is associated with the anthropomorphization of robots, which are becoming more human-like. Robots’ increasing similarity to humans could therefore lead to the endangerment of humans and the criminal responsibility of others. I propose two recommendations in terms of robot design to ensure the supremacy of human life over that of humanoid robots.